Fiscal and Monetary Nexus in Emerging Market Economies : How Does Debt Matter? - Vasishtha, Garima (IMF Working Papers; Working Paper ;, 2006)
This paper examines two main aspects of the interaction between fiscal and monetary policy in emerging market economies. First, it explores the interest rate-inflation relationship in economies with different levels of external and domestic public debt using panel- and crosssection data. The results show that interest rate-inflation elasticity weakens with debt/GDP and external debt/GDP. Second, it utilizes high-frequency data from Brazil, Turkey, and Poland to examine how market-determined variables react to economic news. The results suggest that when vulnerabilities are high, budget news has the most significant impact on country spreads and interest rates, and the impact of monetary policy is weakened.